In North-Eastern India… Technologies to make food-and livelihood-secured - Sivakumar, P. Sethuraman; Anantharaman, M.; Misra, R. S.; Laxminarayana, K.; Jha, A. K. (Indian Horticulture, 2019)
The CTCRI-NEH programme is one of major technology intervention programmes implemented in the NEH Region. By linking production with processing and markets, it integrates a value chain approach with the livelihood framework to develop sustainable systems. Through this programme, the CTCRI has entered a prestigious league of dedicated agencies that work towards the development of NEH Region, and dedicated work of CTCRI team will leave a indispensable mark in the livelihood of NEH people in the coming years.